전투기 레이다의 시계 외 중거리 공대공 유도탄 데이터링크 연동방안 연구 - 김용민; Yong-min Kim (한국항행학회논문지, 2023)
전투기는 적의 공대공 위협에 대응하기 위해 탐색기(seeker)가 탑재된 유도탄을 운용한다. 단거리 유도탄(SRM; short range missile)은 주로 IR 탐색기를 탑재하고 시계 거리 밖의 표적에 대응하는 중거리 유도탄(MRM; medium range missile)은 대개 RF 탐색기를 장착한다. 중거리 유도탄은 발사되더라도 탐색기의 탐지범위에 도달할 때까지 탐식기가 작동하지 않으며 항공기에 탑재된 레이다로 중거리 유도탄을 일정 거리만큼 유도해야 한다. 이런 유도 방식을 MDL (missile data link)이라 하며, 유도탄의 통신 방식에 따라 단방향 방식과 양방향 방식이 있다. 본 논문에서는 이 두 가지 통신 방식에 따른 MDL과 이를 위한 레이다, 임무컴퓨터 및 유도탄 간의 연동에 대해 논하고자 한다. Fighter jets employ guided missiles equipped with seekers to counter enemy air threats. Short range guided missiles(SRM) usually carry infrared(IR) seekers and are used to engage targets within visual range. On the other hand, medium range guided missiles(MRM) often utilize radio frequency(RF) seekers to engage targets beyond visual range. Medium range guided missiles do not activate their seekers until they reach the detection range of the seeker, and the aircraft's radar guides them for a certain distance. This guidance method is called Missile Data Link(MDL), and it can be implemented in either one-way or two-way communication modes, depending on the missile's communication system. In this paper, we discuss MDL based on these two communication modes, along with the integration of RADAR, mission computers, and guided missiles.